OUTCOME OF EXPERIENTIAL LEARNING: A QUASI EXPERIMENTAL STUDY - Nasreen, Maimoona; M. Janjua, Qasim; Azhar, Tayyaba; Leghari, Qurrat-ul-ain; Malik, Samina (Pakistan Journal of Physiology, 2018)
Background: The practical curriculum of 2nd year medical students mainly consists of neurological examination. Objective of this study was to see the effect of experiential learning on performance of medical undergraduates during examination of cortical and peripheral perceptions. Method: In this quasi experimental study, 142 students of 2nd Year MBBS, University College of Medicine and Dentistry were inducted and Experiential Learning cycle was used as a teaching and learning intervention. This cycle was run in 4 stages: Concrete experience, Observation and reflection, Formation of abstract concepts (analysis) and generalizations (conclusions), and Hypothesis testing leading to new experiences. A conventional practical demonstration was given followed by hands-on training by trained Demonstrators. The students were assessed at observed OSPE stations. Their performance was video-recorded for reflection. The students then reflected on performance videos (reflection on action). They were asked to identify and quote their strengths and weaknesses. They were then subjected to small group discussion/peer-assisted learning. The students evaluated each other with the help of standardized key. In late session exams the students’ final score was recorded. Their performances before and after reflection were compared through paired sample Student’s t-test. Results: There were highly significant differences in scores (p=0.006) before and after implementation of the experiential learning cycle. Conclusion: Academic performance of students can significantly improve by implementation of experiential learning.